2012
DOI: 10.1128/jvi.00247-12
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomaviruses Recruit Cellular DNA Repair and Homologous Recombination Factors to Viral Replication Centers

Abstract: Human papillomaviruses (HPV) activate the ataxia telangiectasia mutated (ATM)-dependent DNA damage response to induce viral genome amplification upon epithelial differentiation. Our studies show that along with members of the ATM pathway, HPV proteins also localize factors involved in homologous DNA recombination to distinct nuclear foci that contain HPV genomes and cellular replication factors. These studies indicate that HPV activates the ATM pathway to recruit repair factors to viral genomes and allow for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
215
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(243 citation statements)
references
References 45 publications
17
215
0
3
Order By: Relevance
“…It was recently shown that by activating the ATM pathway, HPV recruits cellular DNA repair and recombination factors into its replication centers during the stable and vegetative phases of its life cycle (62). Our observations that ␥H2AX, ATRIP, and TopBP1 are mobilized into HPV replication centers indicate that during the transient-replication phase, HPV replication also activates the ATR pathway (Fig.…”
Section: Fig 9 U2os Cells Were Transfected With 2 G Of the Hpv18/e8supporting
confidence: 50%
“…It was recently shown that by activating the ATM pathway, HPV recruits cellular DNA repair and recombination factors into its replication centers during the stable and vegetative phases of its life cycle (62). Our observations that ␥H2AX, ATRIP, and TopBP1 are mobilized into HPV replication centers indicate that during the transient-replication phase, HPV replication also activates the ATR pathway (Fig.…”
Section: Fig 9 U2os Cells Were Transfected With 2 G Of the Hpv18/e8supporting
confidence: 50%
“…At present, we can only speculate that this increase in ROS and oxidative DNA damage may contribute to viral genome production. Recent studies suggest that the introduction of doublestrand DNA breaks into HPV DNA during productive replication is an important step in HPV genome amplification and genome maturation (49). Studies have also shown that exposure of cells that normally maintain episomal copies of the HPV genome to physiologically high doses of nitric oxide can lead to upregulation of early E6 and E7 oncogene expression, as well as to a significant increase in DNA double-strand breaks (16).…”
Section: Discussionmentioning
confidence: 99%
“…In the viral life cycle, HPV replication is initiated by E2 binding and recruitment of the E1 helicase to the OR (McBride 2008). It also depends on activation of the DNA damage response by ATM (Gillespie et al 2012) and ATR (Reinson et al 2013). Therefore, looped structures and associated rearrangements could be byproducts of aberrant HPV integrant replication.…”
Section: Discussionmentioning
confidence: 99%